Pengaruh Experience Value Terhadap Repurchase Intention Pelanggan Shoope Di Bandung Pada Tahun 2023 - Rozi, Fakhrul; Hidayat, Rahmat (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Technology that develops continuously certainly creates a big impact on various fields, one of which is the creation of E-commerce in the business world. Shopee is the leading online shopping platform in Southeast Asia and Taiwan headquartered in Singapore. Shopee comes in the form of mobile applications and websites to make it easier for users to do online shopping activities. The features provided by Shopee itself adjust to each region of the country in facilitating their customers so that they can create easy, safe, and fast buying and selling transactions with strong payment and logistical support. This study aims to determine the experience value and repurchase intention of Shopee customers and also to determine the experience value of Shopee customer repurchase intention in 2023. The research method used in this research is quantitative descriptive method. The results of this study confirm that there is a positive and significant influence between customer experience (experience value) and Shopee customer repurchase intentions, indicating that the value of customer experience has a very significant impact on the desire to make repeat purchases. Keywords: Shopee, Experience Value, Repurchase Intention